Lignocellulosics as sustainable resources for production of bioplastics: a review - Brodin, Malin (2017)
The bio-based economy requires a sustainable utilization of bioresources for production of a range of products, including pulp, paper, chemicals, biofuel and bioplastics. Currently, various types of bioplastics are produced industrially, competing in performance and price with the conventional fossil-oil based plastics. However, there is also a major interest in utilizing non-food crops, such as lignocellulosics, for production of drop-in polymers or new dedicated bioplastics. Lignocellulosic resources have a potential to replace plastics and materials, which have been traditionally based on fossil resources. This is important, as the development of high performance bio-based and renewable materials is one important factor for sustainable growth of the bio-based industry. However, production of bioplastics from forestry biomass requires a dedicated fractionation into the major components, i.e. cellulose, hemicelluloses and lignin, effective purification processes and cost-effective routes for conversion into monomers and platform molecules, utilized as a basis for bioplastics production. These processes are now technologically demanding and not profitable. The intention of this work was thus to review the current advances that have been made during the years within fractionation and purification of lignocelluloses and the processes that may feasible for production of bioplastics, based on wood components.